Routine noninvasive prenatal screening for fetal Rh D in maternal plasma—A 2‐year experience from a single center in Belgium. Issue 5 (30th March 2022) - Blomme, Siska; Nollet, Friedel; Rosseel, Wesley; Bogaard, Natalie; Devos, Helena; Emmerechts, Jan; Cauwelier, Barbara
Abstract: Background: Hemolytic disease of the fetus and newborn (HDFN) due to rhesus D (RhD) immunization is a potentially life‐threatening situation for which use of Rh Immunoglobulin (RhIg) has decreased risk drastically. Determination of fetal RHD on maternal plasma can be used to restrict prenatal RhIg administration to women carrying an RhD‐positive child, avoiding unnecessary administration of blood‐derived products. Study Design and Methods: The aim of this study is to determine the performance of fetal RHD typing in our center. We prospectively collected 205 fetal RHD and 127 serological cord blood RhD data from RhD‐negative women starting at 11 weeks of pregnancy (from October 2019 to October 2021). Real‐time polymerase chain reaction targeting RHD exon 5 and 7 was used, similar to the screening program in The Netherlands, supplemented with an amplification control (beta‐actin; ACTB) and a sex determination marker located on the Y‐chromosome (SRY gene). Results: Fetal RHD testing reached a sensitivity and specificity of 100%. No false‐negative nor false‐positive results were reported. Inconclusive results (6%, 13/205) were due to weak amplification in 10 cases, a maternal RHD variant in 2 cases (RHD*01N.71 and partial DVI), and a fetal RHD variant (partial DVI) in 1 case. Unnecessary administration of RhIg prophylaxis was avoided in 33% of cases and on the other hand was administered in one case (fetal partial DVI) which would have been missed with cord blood serology. Discussion: This study demonstrates the high accuracy of routine prenatal fetal RHD gene screening after 11 weeks of pregnancy, encouraging routine clinical practice.